2021
DOI: 10.47836/pjssh.29.3.14
|View full text |Cite
|
Sign up to set email alerts
|

“Please Stay, Don’t Leave!”: A Systematic Literature Review of Safeguarding Intangible Cultural Heritage in the Fourth Industrial Revolution

Abstract: Intangible cultural heritage (ICH) has been recognised as an indicator of the tangible heritage’s cultural diversity, which contains inherent characteristics of the community’s knowledge, practices, expressions and skills. Thus, various actions of support and collaboration to safeguard the global cultural diversity were conducted, preventing the deterioration and destruction of intangible heritage, which paved the way for the Fourth Industrial Revolution (IR 4.0). This study aimed to examine the safeguarding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Additionally, seven studies were identified as literature reviews. They are of great importance for the development of future studies as they analyze the potential impacts of the fourth industrial revolution in the tourism industry in distinct settings, such as cultural heritage protection [ 59 ], education [ 60 ], hospitality [ 8 ], pandemic crises [ 61 ], small island developing states [ 62 ], and social entrepreneurship [ 63 ]. Also, the prospects of blockchain are explored in the study by Ref.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Additionally, seven studies were identified as literature reviews. They are of great importance for the development of future studies as they analyze the potential impacts of the fourth industrial revolution in the tourism industry in distinct settings, such as cultural heritage protection [ 59 ], education [ 60 ], hospitality [ 8 ], pandemic crises [ 61 ], small island developing states [ 62 ], and social entrepreneurship [ 63 ]. Also, the prospects of blockchain are explored in the study by Ref.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…It is often combined with the LDAvis toolkit 6 to visualize text data. The protection of ICH is an important way to maintain the world's cultural diversity 7 . The effectiveness of mass media has been validated in areas such as public health prevention education 8 and legal awareness education 9 , indicating the necessity of utilizing mass media for public education on ICH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To implement these protection and development strategies, inheritors of ICH achieve the generation of intangible cultural heritage by mobilizing their physical and mental senses and using certain material tools [13]. ICH inheritance mainly takes the form of community inheritance worldwide [14]. Research on inheritors has mainly focused on the skills and traditional culture of ethnic 2 of 17 minorities [15].…”
Section: Introductionmentioning
confidence: 99%